Effect of Industrialization on Taxes from Income, Profit and Capital Gains Among Sub-Sahara African Countries - Busari, Tajudeen Abimbola; Dada, Samuel Olajide; Adegbie, Festus Folajimi; Ogundajo, Grace Oyeyemi (Archives of Business Research, 2024)
Tax revenue is a crucial financial resource for governments worldwide. Developed nations often secure ample tax revenue through robust industrial performance. In contrast, developing economies struggle with various challenges that hinder tax revenue from sources such as income, profit, and capital gains, largely due to high unemployment and inadequate industrialization. This study employed an ex-post facto research design and analyzed panel data from 38 countries over 21 years (2001–2021), sourced from the World Bank Group Database. The System Generalized Method of Moments (SGMM) analysis revealed that industrial performance significantly impacts tax revenue from income, profit, and capital gains in sub-Saharan African countries. The study concluded that advancing industrialization in sub-Saharan Africa is essential for maximizing tax revenue from these sources. It is recommended that governments in the region focus on accelerating industrial growth as a strategy to achieve sustainable tax revenue generation.